Top-down approach to design the relief system in a metropolitan city using UAV technology, part I: the first 48 h - Vizvari, Bela; Golabi, Mahmoud; Nedjati, Arman; Gumusbuga, Ferhat; Izbirak, Gokhan (Springer, 2019)
In this study, a relief system for a large metropolitan city exposed to serious earthquakes is designed and a top-down approach is applied. Afflicted people's states and needs are investigated, and the tasks of the system are defined accordingly. The paper focuses on the tasks of the first 48 h of the post-disaster period and, however, shortly mentions the medium-term and the long-term tasks as well, including relief chain, infrastructure rebuilding, fundraising, and debris collection. The monitoring and transportation platform of the system is based on utilizing UAV technology. A Disaster Command Center controls the system and the related departments. The study discusses the different transportation modes for post-disaster relief distribution and the preference for multimodal methods. Finally, the next level of current approach is clarified and new questions are proposed for further investigations.
Keywords: Earthquake; Post-disaster response; Relief distribution system; UAV; Top-down approach